2013
DOI: 10.1002/bbb.1462
|View full text |Cite
|
Sign up to set email alerts
|

Comparative techno‐economic analysis and reviews of n‐butanol production from corn grain and corn stover

Abstract: This work presents a detailed review and comparative analysis of the process design and economics of n-butanol production using corn grain and corn stover. This includes reviewing the most recent n-butanol technologies; demonstrating the impact of key parameters (e.g. plant capacity, raw material pricing, yield) on the overall n-butanol process economics; and comparing how cellulosic biomass conversion technologies and challenges differ from traditional sugar-based n-butanol conversion technology. A major chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 76 publications
(114 reference statements)
2
85
1
Order By: Relevance
“…Bio-ethanol is mainly produced by the fermentation of sugar containing material (starch and sugar based stocks such as sugar cane, corn etc.) by yeast (4). Bio-ethanol is now widely used as a gasoline additive, with the objective to reduce the fossil fuel content in the automobile fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-ethanol is mainly produced by the fermentation of sugar containing material (starch and sugar based stocks such as sugar cane, corn etc.) by yeast (4). Bio-ethanol is now widely used as a gasoline additive, with the objective to reduce the fossil fuel content in the automobile fuel.…”
Section: Introductionmentioning
confidence: 99%
“…'Classically' biobutanol is provided by fermentative pathways like the ABE (acetone, butanol, ethanol) fermentation; the main disadvantages of all these processes and the reason why they are hardy realised for the time being are the poor yields and selectivity to butanol for most of these processes (Tao et al, 2014). Additionally the production of biobutanol uses the same resources as the production of ethanol but the yields are significantly lower and the biocatalysts as well as process technology applied are not fully optimised yet.…”
Section: Butanolmentioning
confidence: 99%
“…Studies have pointed out the advantages of n-butanol as fuel in comparison with ethanol: n-butanol contains a longer hydrocarbon chain being more similar to gasoline (both are hydrophobic); may be mixed with gasoline and diesel at higher proportions [5,6]; Mendez et al [7] concluded that blends of butanol with jet fuel present promising performance; according to Tao et al [8], butanol fuel efficiency may equal that of gasoline; it may be used as oxygenate to allow more complete combustion, reducing carbon monoxide emissions [9]; it is capable of performing better for an http engine's cold start and may also be used as an additive to ethanol for that function [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, simulation can provide data required for estimation of economic [8,17,19,31,28,[32][33][34][35][36][37] and environmental performance [33,[38][39][40][41][42][43]. Previous recent studies from the authors of this paper have evaluated technical aspects and economics of n-butanol production from sugarcane sugars [17,32] and ethanol catalysis [19,30,44], as well as the environmental performance of the ABE process in a sugarcane biorefinery [42].…”
Section: Introductionmentioning
confidence: 99%